Inducible T‐cell costimulator (ICOS) and CD28 polymorphisms possibly play a role in the pathogenesis of chronic autoreactive urticaria. (1st December 2017) - Brzoza, Z.; Grzeszczak, W.; Trautsolt, W.; Moczulski, D.
Summary: Background: Clinical experience emphasizes the coexistence of chronic spontaneous urticaria (CSU) and autoimmune disturbances. In chromosome 2q33‐34, there is a cluster of homologous genes that are considered promising candidate genes for susceptibility to autoimmune diseases. Aim: To examine the possible role of polymorphisms in the genes for CD28 and inducible T‐cell costimulator (ICOS) in the background of CSU. Methods: In total, 149 patients with CSU with positive autologous serum skin test were enrolled in the study. The healthy control (HC) group consisted of 100 healthy volunteers. In all subjects, the CD28 rs2140148 and rs3116496 and the ICOS rs6726035 polymorphisms were analysed. Disease severity was assessed by means of Urticaria Activity Score. Results: We found a statistically significantly lower prevalence of the ICOS rs6726035 TT genotype among patients with CSU compared with HCs. Furthermore, the haplotype rs2140148A, rs3116496T and rs6726035C presented a possible association with CSU. We did not find any association between the examined polymorphisms and either urticaria severity or age of disease onset. Conclusions: Our results underline the role of autoimmune components in the pathogenesis of chronic autoreactive urticaria, and indicate it as a potentially genetically related disorder.